Interactive Mobile Application in Learning Iban Language - Jeckie, Valerie; Ariffin, Asma Hanee (International Journal of Recent Technology and Applied Science (IJORTAS), 2023)
My Iban application is an interactive mobile application for learning the Iban language. The aim of this study is to develop a mobile application that is focusing on creating alternative tools in learning Iban language where it will ease the students to learn. This application development is based on the problem that occurred when there is no suitable application in learning Iban language among the students in primary school. The methodology that has been chosen in developing the application is the Evolutionary Prototyping model. Quantitative technique is used to test and evaluate My Iban applications. Based on the findings obtained from the users through a survey, it finds out that My Iban application have gained positive feedback. The functionality and the usability of My Iban application has been tested and approved by the user. For future works, the use of interactive multimedia elements in developing mobile applications need to be improved. In conclusion, the application hopefully can encourage the students to learn the Iban language better via mobile application.